THE AESTHETIC JUDGMENT OF BEAUTY. THE SUBLIMITY IN ART AND KANDINSKY´S THOUGHT (Andamios, Revista de Investigación Social, 2009)
The Kritik der Urteilkraft is a fundamental piece in the history of art. Kant develops the two categories that mark an important division. The category of beauty predominates in the paradigm of classic art; representation, which is a determined form, prevails in the composition of the work. The category of sublime breaks with the limits imposed by the form, letting the deepest feelings of the human being appear. Kandinsky is the first one to pass over form to get into abstraction, reaching a more pure way of expression. This painter shows in the material support the “internal element”; his work moves away from the category of beauty and the prototypal representation. His art settles what is sublime for the artist.
Keywords: Art; Kant; beauty; sublime; Kandinsky